Minat konsumen terhadap pembelian ulang produk coca-cola kemasan keluarga - DENNY SEPTA HARYANTI (Pusat Penelitian dan Pengabdian Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2015)
The research problem is how to conceptualize the product quality, service quality, consumer satisfaction and its dimensions, and could contextually product quality and service quality influence satisfaction based on consumer need in order to increase product repurchase. To answer the question on this study, research model was developed. The model has four dimension: product quality, service quality, consumer satisfaction and repurchase with three hypothesis tested. Data analysis over 100 respondents who have already consumed Coca-Cola beverage (home consumption package) in Pasadena and Tlogosari area in Semarang was done using Structural Equation Modeling as analysis tool. The result showed that all hypothesis tested was not rejected, and we concluded that product and service quality has a positive impact for consumer satisfaction and product repurchase.